If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 1 + -2m + 3m Combine like terms: -2m + 3m = 1m 2 = 1 + 1m Solving 2 = 1 + 1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 2 + -1m = 1 + 1m + -1m Combine like terms: 1m + -1m = 0 2 + -1m = 1 + 0 2 + -1m = 1 Add '-2' to each side of the equation. 2 + -2 + -1m = 1 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 1 + -2 -1m = 1 + -2 Combine like terms: 1 + -2 = -1 -1m = -1 Divide each side by '-1'. m = 1 Simplifying m = 1
| 3=-1 | | R(p)=-4p^2+24000p | | 1=n+1+2n | | 2a+3a=-5 | | 75+(4x-9)=180 | | 5(0)=0 | | 3=x-3+2x | | 4+(3+8)=(4+3)+8 | | 1=-3x-3+1 | | H=-16t^2+12t+1700 | | (x-2)/(x^2-x-20) | | (-2/3)*(-4/15)*(45/16) | | 2=1-2m-3m | | n-1-3=-7 | | -2=-3n+n | | (3j+k)+(-4j-7k)-(j+k)= | | -8=-2+3k-3 | | -[3h+5y]-[7y+h]= | | 3u-3=-18 | | 180=(x+2)(5x+35) | | (2x^2-5x+6)*(3x^4-5x^3-6x^2+4x-3)= | | X+(X*.08)=40.75 | | X+(X*.1)=41.24 | | -3.2y+2.38=3.7 | | 4.7=-8.3-d | | .4x-0.7=.3x+7 | | (3x^2-5x)*(2x^3+4x^2-x+2)= | | Y^2-20y+100=y-8 | | 5x^3-26x^2+25=0 | | x*x*x-2x=21 | | Y^2-20y+108=0 | | 4r+20=-5r+34 |